Anticholinergic Use and Recurrent Falls in Community-Dwelling Older Adults: Findings From the Health ABC Study. (November 2015) - Marcum, Zachary A.; Perera, Subashan; Thorpe, Joshua M.; Switzer, Galen E.; Gray, Shelly L.; Castle, Nicholas G.; Strotmeyer, Elsa S.; Simonsick, Eleanor M.; Bauer, Douglas C.; Shorr, Ronald I.; Studenski, Stephanie A.; Hanlon, Joseph T.; et al.
Background: Although it is generally accepted that anticholinergic use may lead to a fall, results from studies assessing the association between anticholinergic use and falls are mixed. In addition, direct evidence of an association between use of anticholinergic medications and recurrent falls among community-dwelling elders is not available.Objective: To assess the association between anticholinergic use across multiple anticholinergic subclasses, including over-the-counter medications, and recurrent falls.Methods: This was a longitudinal analysis of 2948 participants, with data collected via interview at year 1 from the Health, Aging and Body Composition study and followed through year 7 (1997-2004). Self-reported use of anticholinergic medication was identified at years 1, 2, 3, 5, and 6 as defined by the list from the 2015 American Geriatrics Society Beers Criteria. Dosage and duration were also examined. The main outcome was recurrent falls (≥2) in an ensuing 12-month period from each medication data collection.Results: Using multivariable generalized estimating equation models, controlling for demographic, health status/behaviors, and access-to-care factors, a 34% increase in likelihood of recurrent falls in anticholinergic users (adjusted odds ratio = 1.34; 95% CI = 0.93-1.93) was observed, but the results were not statistically significant; similar results were found with higher doses and longer duration of use.Conclusion: Increased point estimates suggest an association of anticholinergic use with recurrent falls, but the associations did not reach statistical significance. Future studies are needed for more definitive evidence and to examine other measures of anticholinergic burden and associations with more intermediate adverse effects such as cognitive function.